2013
DOI: 10.1371/journal.pone.0063770
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Prevents Hepatic Steatosis and Injury Induced by a High-Fat Diet in Hamsters

Abstract: BackgroundNuciferine is a major active aporphine alkaloid from the leaves of N. nucifera Gaertn that possesses anti-hyperlipidemia, anti-hypotensive, anti-arrhythmic, and insulin secretagogue activities. However, it is currently unknown whether nuciferine can benefit hepatic lipid metabolism.Methodology/Principal FindingsIn the current study, male golden hamsters were randomly divided into four groups fed a normal diet, a high-fat diet (HFD), or a HFD supplemented with nuciferine (10 and 15 mg/kg·BW/day). Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 38 publications
11
79
0
Order By: Relevance
“…Imbalances in hepatic lipid metabolism lead to the accumulation of hepatic TG and insulin resistance, finally causing diabetes (Perry et al ., ). The plasma lipid profile of nuciferine‐treated diabetic mice in our study showed similar trends to that seen with the HFD‐fed hamster model treated with nuciferine (Guo et al ., ). In addition, p.o.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Imbalances in hepatic lipid metabolism lead to the accumulation of hepatic TG and insulin resistance, finally causing diabetes (Perry et al ., ). The plasma lipid profile of nuciferine‐treated diabetic mice in our study showed similar trends to that seen with the HFD‐fed hamster model treated with nuciferine (Guo et al ., ). In addition, p.o.…”
Section: Discussionmentioning
confidence: 97%
“…Nuciferine (PubChem CID: 10146, Figure 1A), an aromatic ringcontaining alkaloid, isolated from the leaves of Nelumbo nucifera, has been used in traditional Chinese medicine for treating obesity, heliosis and bleeding (Ono et al, 2006;Wang et al, 2015;Sharma et al, 2017). It has also been shown to alleviate dyslipidemia and hepatic steatosis in high-fat diet (HFD)-fed hamsters (Guo et al, 2013). However, whether nuciferine ameliorates liver injury in diabetic conditions and the molecular mechanism(s) of such potential actions is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…NF was also found to reduce the development of atherosclerosis via inhibition of vascular smooth muscle cell proliferation and migration (Ho et al, 2010). Moreover, many in vivo studies have demonstrated that NF displays beneficial effects on non-alcoholic fatty liver disease, HIV, and melanoma (Guo et al, 2013;Kashiwada et al, 2005;Nakamura et al, 2013). However, it is still not clear whether NF, as a potential anti-cancer agent, may suppress tumor progression by directly affecting tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity‐associated fatty liver has been linked to tissue inflammation (Guo et al ., ). As expected, the healthy hamsters (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, RBNE supplementation significantly increased hepatic protein levels of PPAR-alpha. These results suggested that the beneficial effects of RBNE in the treatment of liver steatosis might be partly due to enhanced free fatty acid (FFA) oxidation and lipid export in the liver (Guo, 2013). It had been reported that many of the cardiovascular benefits of soybean may be related to isoflavones (Clarkson, 2002).…”
Section: Discussionmentioning
confidence: 99%